NONFERROUS WASTE AERATED CONCRETE - Elesin, Mikhail A.; Mashkin, Nikolay A.; Karmanovskaya, Natalia V. (Journal of Applied Engineering Science, 2021)
This article presents studies of the technological process for producing curing monolithic aerated concrete from industrial slag sands. The purpose of this work is to develop and optimize the composition of lightweight concrete using gypsum building plaster as a binder. For the construction of low-rise industrial buildings, it is proposed to use industrial slag components and waste from the Norilsk industrial district. To form a cellular structure of concrete, itwas chosen the chemical method of porosity, which involves the implementation of a gas evolution reaction when aluminum powder interacts with calcium hydroxide. During the tests, Portland cement M400 of the Topkinsk cement plant was used, sand with a specific surface area of 4.62; 7.3; 16.48 and 28.85 m²/kg. The study of the parameters characterizing the blowout and structure formation of aerated concrete mixture was carried out in collapsible metal shapes with a base of 0.10*0.10 m, filled to 1/3 of the height. Temperature profiles were recorded by controlling 10 thermocouples for 1-2 minutes using a КСП potentiometer. It was concluded that expanded clay aggregate and sawdust for gypsum-lightweight concrete are active and contribute to its hardening.